Phosphorus fertilizer use in pineapple cultivation with in situ residues burning on organic soils - Ahmed, Osumanu Haruna; Mohd Hanif, Ahmad Husni; Musa, Mohamed Hanafi; Abd Rahim, Anuar; Syed Rastan, Syed Omar (Taylor & Francis, 2007)
In Malaysia, pineapples are grown on peat soils, but most phosphorus (P) fertilizer recommendations are made without due quantification of P uptake; the distribution of P in roots, stem, leaves, peduncle, fruit, and crown; or loss through leaching even though P retention in peat soils is low. This study was conducted to determine applied P-use efficiency under a conventionally recommended fertilization regime in pineapple cultivation with in situ residues burning before replanting. Results showed that most of the P uptake in pineapple can be found in the fruit, stem, leaves, and crown, but the general trend of P distribution was in the order of fruits > leaves > stem > crown > peduncle > roots. Phosphorus recovery in pineapple cultivation was about 40%, and this low recovery was attributed to leaching. Hence, fertilizer recommendations need to take into consideration P loss through leaching. This will help to increase P-use efficiency because it is not possible to build up P content of peat soils. As a result, the need to assess the possibility of side-dress applications of phosphatic fertilizers on peat soil is necessary. Copyright © Taylor & Francis Group, LLC.